Cracking the Egg Potential: Traditional Knowledge, Attitudes, and Practices in a Food-Based Nutrition Intervention in Highland Ecuador. Issue 2 (June 2018) - Waters, William F.; Gallegos, Carlos Andres; Karp, Celia; Lutter, Chessa; Stewart, Christine; Iannotti, Lora
Background: Food-based interventions can reduce the prevalence of undernutrition and improve household food security, but nutritious and accessible foods may be underutilized. In Ecuador, eggs are inexpensive and widely available, but while they are a valuable source of essential nutrients for infants and young children, medical advice and community-based information have limited their inclusion in infants' diets. Objective: A qualitative component was conducted to understand local perceptions, knowledge, and practices to complement a randomized control trial that studied the effect of introducing eggs on nutritional status and growth in infants from 6 to 9 months in rural communities in the highland province of Cotopaxi, Ecuador. Methods: The qualitative inquiry consisted of key informant interviews, focus group discussions (FGDs), and structured observations in order to understand perceptions, knowledge, and practices related to household egg consumption and to the introduction of eggs in infants' diets. Results: The two principal findings were that: (i) eggs are an available and culturally acceptable food source although they are not always a part of the diet; and (ii) perceptions and practices related to household consumption and the introduction of eggs into the diet of infants are shaped by local knowledge and practices, which are shaped by biomedical information and advice provided by public health professionals. Conclusion: Through an effective food-based intervention that includes qualitative research and a social marketing component, the behaviors of mothers and other caregivers can be modified, enabling children to realize the nutritional advantages of early introduction of eggs into their diet.